2020
DOI: 10.3389/fmolb.2020.609088
|View full text |Cite
|
Sign up to set email alerts
|

Surprisingly Fast Interface and Elbow Angle Dynamics of Antigen-Binding Fragments

Abstract: Fab consist of a heavy and light chain and can be subdivided into a variable (VH and VL) and a constant region (CH1 and CL). The variable region contains the complementarity-determining region (CDR), which is formed by six hypervariable loops, shaping the antigen binding site, the paratope. Apart from the CDR loops, both the elbow angle and the relative interdomain orientations of the VH–VL and the CH1–CL domains influence the shape of the paratope. Thus, characterization of the interface and elbow angle dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…The H4 loop has been traditionally considered to be part of the antibody framework; however, it has been shown not only for antibodies but also for T-cell receptors that the H4 loop can directly interact with the antigen and thus, influence antigen binding (9,40). The fact that one single residue in the H4 loop can determine different paratope conformations in solution strongly supports the idea of highly correlated CDR loop movements, which interconvert into each other on the micro-to-millisecond timescale and favor specific interdomain orientations (12,13,41,62,68,77,78). Considering only one single static structure might not be sufficient to fully understand the consequences of point mutations on the resulting conformational diversity (42,79).…”
Section: Discussionmentioning
confidence: 99%
“…The H4 loop has been traditionally considered to be part of the antibody framework; however, it has been shown not only for antibodies but also for T-cell receptors that the H4 loop can directly interact with the antigen and thus, influence antigen binding (9,40). The fact that one single residue in the H4 loop can determine different paratope conformations in solution strongly supports the idea of highly correlated CDR loop movements, which interconvert into each other on the micro-to-millisecond timescale and favor specific interdomain orientations (12,13,41,62,68,77,78). Considering only one single static structure might not be sufficient to fully understand the consequences of point mutations on the resulting conformational diversity (42,79).…”
Section: Discussionmentioning
confidence: 99%
“…By applying fast Fourier transformation to the interface angles, timescales of 0.1 to 10 GHz could be assigned to the fastest collective interdomain movements, while the slower components of the observed dynamics are governed by conformational changes in the CDR loops that occur in the microto-millisecond timescale. 37,38 In contrast to the prevalent static view of the binding interface, it was shown that antibodies exist as ensembles of paratope states. 39 These paratope states are defined by a characteristic combination of CDR loop conformations and interdomain orientations.…”
Section: Figurementioning
confidence: 99%
“…80,85 Studies investigating the consequences of affinity maturation have observed a substantial rigidification of the antigen-binding site as a consequence of the increase in specificity. 38,39,80,[85][86][87] Even though rigidification might only be one of the various consequences of affinity maturation, it still represents a fundamental mechanism resulting in an increase in specificity (Figure 3).…”
Section: Antibody Specificity -Antibody Affinity Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Already a small number of mutations in the framework regions, in particular in the V H -V L interface, can result in structural changes of the binding site, which consequently influences antigen recognition and can lead to allosteric conformational rearrangements in the constant domains and the elbow angle (25)(26)(27)(28)(29)(30). The majority of Fab interface dynamics have been reported to occur in the low nanosecond timescale, while slower components of the movements are dominated by conformational rearrangements in the CDR loops in the microto-millisecond timescales (18,31,32). Based on these observations, antibodies were previously described as ensembles of paratope states in solution, which are characterized by a combination of correlated CDR loop conformations and interdomain orientations, which interconvert into each other by synchronous loop and interdomain rearrangements (33).…”
Section: Introductionmentioning
confidence: 99%